A Review of Bioactive Compounds in Oyster Shell and Tissues - Ulagesan, Selvakumari; Krishnan, Sathish; Nam, Taek-Jeong; Choi, Youn-Hee (Frontiers in Bioengineering and Biotechnology, 2022)
Oysters are saltwater bivalves with high nutritional and medicinal value that are consumed widely around the world. As well as being highly nutritious, oysters are a low-calorie, low-cholesterol source of protein and an exceptional source of zinc, which strengthens the immune system; and a rich source of bioactive compounds, which comprise various biological activities. The present review summarizes the biological applications and bioactive compounds from oyster shells, whole tissue, gill tissue, and mantle tissue. The various biological compounds present in an oyster shell, and their chemical constituents, have applications in the food, pharmaceutical, and medical industries. Bioactive peptides and proteins obtained from the whole, mantle, and gill tissues of oysters exhibit antioxidant, antimicrobial, antihypertensive, anticancer, antifatigue, anticoagulant, and anti-wrinkle effects, as well as enhance osteoblast differentiation. This review clearly shows that oysters have great potential for functional food production and that various compounds therein can have pharmaceutical applications.